An economic and environmentally benign approach for the preparation of monolithic silica aerogels. Issue 96 (29th September 2016) - Zhang, Yuanyuan; Peng, Junxia; Du, Guanqun; Zhang, Hongxia; Fang, Yu
Abstract : One step sol–gel reaction, followed by solvent exchange free ambient pressure drying resulted in various monolithic silica aerogels from super-hydrophobic to hydrophilic with densities as low as 0.026 g cm −3 and thermal conductivities lower than air. Abstract : Troublesome drying has always limited the scale-up production and wide-spread application of monolithic aerogels because of the high energy consumption and/or organic solvent utilization. In this report, a gel-emulsion-based one step method was developed for the facile, economic and environmentally friendly preparation of various monolithic silica aerogels. The wet porous silica formed in these systems could be dried at ambient-pressure without the need for solvent exchange. It was demonstrated that the stabilities of the gel-emulsions and the resultant wet porous silica gels originate from the utilization of a specially designed stabilizer, which is a derivative of cholesterol (Chol-OH ). With the aid ofChol-OH, the chemical functionalities and the densities of the monolithic silica aerogels could be largely tuned via simple variation of the structures of the precursors, organosilanes, and water content in the gel emulsions. As examples, monolithic silica aerogels from super-hydrophobic (water contact angle larger than 150°) to hydrophilic (water contact angle lower than 25°) and those with a density as low as 0.026 g cm −3 were obtained. Moreover, the internal structures of the aerogels can also be tuned by adjusting the reaction rate of the sol–gel process. Morphology studies revealed that the as prepared monolithic silica aerogels possessed inter-connected highly porous structures, and the pore walls are composed of highly ordered meso-pore structures with an average size of ∼25 nm. Their thermal conductivities at ambient pressure, humidity, and temperature (30 °C) were as low as 20.6 mW m −1 K −1, which is 18% lower than that of the reference air (24.4 mW m −1 K −1 ). Considering the ease of the stabilizer preparation, the gel emulsions, and the characteristics of the aerogel preparation process, we believe that the strategy developed in the present work represents substantial progress in the field of aerogel preparation, and the monolithic silica aerogels created have great potential for real-life applications.